Using cluster analysis as a method of classification of the genus Salix L. representatives - М. В. Роїк; В. В. Баликіна (Plant Varieties Studying and Protection)
Purpose. To study interactions among the representatives of the genus Salix L. through the cluster analysis, form groups of closely related species and hybrid forms basing on differences of morphological parameters of leaves. Methods. Field, cluster analysis and tree graphics. Results. Willow species were grouped according to absolute parameters of leaf, and three groups of clusters were identified. The degree of affinity between species were assessed using values of an Euclidean distance. Distinctive features of leaf parameters were defined: length of a leaf blade (Ll), distance (cm) between the leaf tip and its maximum width (SDmxT) and the distance between the leaf tip (cm) and the line of its width that corresponds to the length of petiole (SLpT). Conclusions. Using the willow species collection as an example, diagnostically valuable quantitative parameters of leaves were revealed, the use of which allows to identify willow species and hybrid forms through PC applications.